Biologi Reproduksi Ikan Pari Toka-Toka (Himantura walga, Muller dan Henle 1841) yang Tertangkap dan di Daratkan di Cilincing - Novariani, Novariani; Lubis, Hafni; Fahmi, Fahmi (Bioma, 2014)
Abstract Rays are cartilaginous fishes that are commonly caught by fishermen in Java Sea especially in Jakarta Bay. One species of rays that has been oftenly caught is Himantura walga. Even though they are not categorized as target fishes, rays are susceptible to excessive fishing, due to their biological characteristics, so an effort is needed to conserve these fishes in the nature. As a first step to their conservation, an initial survey about its reproduction was done for Himantura walga. The survey covered spread of width size, sex ratio, growth pattern, sexual maturity level and the width size of males and females when they reach sexual maturity. Method used was descriptive with both market and purposive sampling. Chi square analysis showed that male and female ratio were well balanced. Result of regression showed that the width-weight correlation between male and female rays was allometrically positive. Most Captured males showed that their sexual maturity were at fully calcified stage (FC) while most females were at immature stage (TKG 1), according to their gonad condition. Males tend to reach sexual maturity earlier and have smaller body than females. Hence, it is advised for the fishermen to use selective fishing gears that are only able to capture adult rays. Key words: Himantura walga, rays, reproduction biology